إشكالية الدفع بعدم دستورية المعاهدات الدولية على ضوء المادة 188 من دستور 2016 والقانون العضوي 18-16 المحدد لشروط وكيفيات تطبيق الدفع بعدم الدستورية: مقارنة بين النظامين المصري والجزائري - وليد، عمار زورقي; زيدومة، درياس (جامعة زيان عاشور الجلفة, 2019)
موضوع المقال يتعلق بنص المادة 188 من الدستور الجزائري لسنة 2016 التي أتاحت للأفراد الدفع بعدم الدستورية، وقد وجاء تطبيقا لهذا النص القانون العضوي رقم 18-16 المحدد لشروط وكيفيات تطبيق الدفع بعدم الدستورية، فهل نص المادة 188 من الدستور أعطي للمجلس الدستوري صلاحية الرقابة البعدية لدستورية المعاهدات الدولية بعد أن تصبح نافذة داخليا، ومن ثمة أصبح بإمكان الأفراد الطعن بعدم دستوريتها؟ أم أن المؤسس الدستوري يقصد فقط التشريعات الوطنية؟ وهل أن المؤسس الدستوري وسع فعلا من الجهات التي يحق لها الطعن بعدم دستورية القوانين والمعاهدات الدولية بموجب التعديلات التي طرأت على دستور سنة 2016؟ أم أن هذا الدستور يعد تراجعا بشأن صلاحيات المجلس الدستوري لدى رقابته على دستورية المعاهدات الدولية. وكيف هو الحال بالنسبة للدستور والتشريع المصري الذي اسند مهمة الرقابة على دستورية القوانين والمعاهدات الدولية للمحكمة الدستورية العليا؟ بعد مقارنة كلا النظامين الجزائري والمصري. في هذا المقال نقوم بتحليل تلك الأوجه المثارة لنبين رأينا في مدى محدودية وقصور رقابة المجلس الدستوري على دستورية المعاهدات الدولية مقارنة بدوره في رقابة على دستورية القوانين وبالمقارنة أيضا مع ما هو جاري به العمل في الدستور والتشريع المصري.
Subject of the article hangs in text of the substance 188 from the Algerian constitution to sharpened 2016 which the individuals allowed for the constitutional pushing in lack, and already and number 16-18 came application consequently the organic text the law definitive for conditions the constitutional pushing in lack, so is text of the substance 188 from the constitution gave for the constitutional council dimensional competence the supervision for constitutionalist of the treaties international, and from then possibility of the individuals became in the defamation in lack constitutional her? Mother that the constitutional founder intends only the national legislations? Is and that the constitutional founder is capacity actually with regard to which be true the constitutional defamation in lack the laws and the international treaties pursuant to the modifications have fun which constitution of year 2016 occurred on? Mother that the constitution raved retreat promises concerning competences of the council constitutional enemy aalrqaabth on constitutionalist of the treaties international. How he the situation in the ratio for the constitution and the legislation the Egyptian legislation who task of the supervision on constitutionalist of the laws supports and the constitutional treaties international for the court high? In the article raved analysis of that faces straightens in agitated with comparison her with the Egyptian regime to gives to patching disagreed our in all question agitated.
Keywords: المعاهدات الدولية -- التشريعات الجزائرية -- المؤسسات الدستورية -- القوانين المصرية